2018
DOI: 10.7762/cnr.2018.7.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Low Handgrip Strength Is Not Associated with Type 2 Diabetes Mellitus and Hyperglycemia: a Population-Based Study

Abstract: Type 2 diabetes mellitus (DM) is commonly linked to muscle weakness and metabolic abnormalities which increase healthcare costs. The study was undertaken to investigate if low handgrip strength, as a marker of muscle weakness, is associated with hyperglycemia and/or DM in Brazilian subjects. In a cross-sectional design, 415 individuals of both sexes (46.7% male) were interviewed by a questionnaire and the DM diagnostic was self-reported. Anthropometric measurements, such as weight, height, body mass index (BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…For TC and LDLC, we only found a significant association with the moderate HGS group, suggesting an inverse U-shaped association between grip strength and TC and LDLC (although we did not find a significant U-shaped association, and data not shown), which was in line with the CoLaus study (the city of Lausanne, Switzerland) (Gubelmann et al, 2017). These findings seem to be in agreement with previous studies (Kawamoto et al, 2016;Lee et al, 2016) but not with another (Giglio et al, 2018). A study of 927 older people in Taiwan found that relative HGS was significantly associated with a favorable lipid profile, including TG, TC/HDLC ratio (Lee et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…For TC and LDLC, we only found a significant association with the moderate HGS group, suggesting an inverse U-shaped association between grip strength and TC and LDLC (although we did not find a significant U-shaped association, and data not shown), which was in line with the CoLaus study (the city of Lausanne, Switzerland) (Gubelmann et al, 2017). These findings seem to be in agreement with previous studies (Kawamoto et al, 2016;Lee et al, 2016) but not with another (Giglio et al, 2018). A study of 927 older people in Taiwan found that relative HGS was significantly associated with a favorable lipid profile, including TG, TC/HDLC ratio (Lee et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Kawamoto et al (2016) showed that weight-adjusted HGS was significantly associated with a favorable lipid profile of TC and HDLC, but not LDLC. However, a cross-sectional study reported that low HGS normalized or not to body weight was not associated with hyperglycemia (Giglio et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A higher prevalence of dynapenia is expected in the CKD population compared to the control group, with the highest prevalence in those with diabetes mellitus. Patients with diabetes appear to have decreased muscle functions [ 53 , 54 ], but this result has been questioned [ 55 ]. We expect different neuromuscular features in CKD patients, specifically for F crit .…”
Section: Discussionmentioning
confidence: 99%